THE MEDIATING ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND SERVANT LEADERSHIP (LITERATURE REVIEW) - Renata Dwiani; Ahmad Badawi Saluy; Didin Hikmah Perkasa (PT. Jurnal Center Indonesia Publisher, 2025)
This literature review aims to explore the influence of emotional intelligence, servant leadership, and organizational commitment on employee career development, with Organizational Citizenship Behavior (OCB) as a mediating variable. The study utilizes a qualitative approach by synthesizing findings from national and international journals published in the past 10–15 years. The results indicate that emotional intelligence enables employees to adapt and interact effectively in the workplace, servant leadership fosters a supportive and empowering work climate, and organizational commitment enhances loyalty and proactive behavior. Furthermore, OCB plays a significant mediating role by reinforcing the relationship between these three variables and career development outcomes. Employees who display high OCB are more likely to gain recognition, trust, and career advancement opportunities. This study highlights the importance of a holistic approach in career development by integrating individual competencies, leadership styles, and affective organizational engagement. Practical implications suggest the need for organizational initiatives that strengthen emotional intelligence, servant leadership, and supportive organizational culture to foster sustainable employee career progression.